Demokrasi Jalan Menuju Kesejahteraan : Studi pada Negara Korea Selatan dan Negara India - Dina Fadiyah; Muhamad Fathan Mandela (Universitas Islam Darul Ulum Lamongan, 2025)
This research aims to explore the role of democracy as a primary instrument in achieving prosperity and the formation of a welfare state, by comparing the experiences of two Asian nations: South Korea and India. Utilizing a qualitative-descriptive approach and library research methodology, this article analyzes how democratic mechanisms influence the distribution of social security and the effectiveness of public policy. The findings indicate that South Korea's democratic transition following the 1980s transformed a previously limited social security system into an inclusive and collaborative model, with national insurance coverage reaching 98.6% of the population by 2018. Conversely, although India stands as the world's largest democracy, it faces significant hurdles in implementing welfare programs— such as the MGNREGA—due to prevailing practices of populism and clientelism that obstruct citizen accessibility. The comparison of these two countries underscores a positive correlation between a high democracy index and the successful development of a welfare state. In conclusion, a healthy and collaborative democracy is not merely a political procedure but a fundamental prerequisite for fostering equitable economic prosperity for all citizens.